Students’ References in Thesis of English Department at STKIP PGRI Sumatra Barat - Yelliza Yelliza (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2016)
It is obvious that referencing is an essential part in scientific writing and ethical values that authors should be used in theirwork. It is strongly informed that reference avoids plagiarism and supports the author arguments. For instance, when a student wrotescientific writing, she or he should quote and cite other related literates or findings to make their writing trustworthy. In other word,it was not just collection of ideas but something authentic and scientific. It was still inchoate if a student who did her thesis withoutstating her or his sources in reference. In fact, the students frequently did not write their citations in reference. It was found that thestudents did not write the sources taken from any experts based on the guideline. They did not write down their references bydetermining the resources from the books, journals, magazine, articles, newspaper, document, thesis, and internet. Most of them onlytended to make their reference from the book. It was not moot point that students did not write about city and publisher in somecases. On the contrary, in advanced writing class, they have been taught how to quote and cite other ideas and how to write them onreferences based on guideline MLA and APA style. Meanwhile, they also had two supervisors to help them during writing their finalproject. Briefly, the result showed that a number of students did not write all their sources and not follow the rule or referenceguideline.